“Literature in culture dialogue”: interuniversity collection of works. Vol.2. Institute of philology, journalism and cross-cultural communication of SfedU. – Rostov-on-Don: Publishing house of science and education fund, 2015. – 447 p. (Proceedings of Southern Federal University. Philology, 2015)
REVIEWS by Kuchumova G.V.